The expansion of TRIAC to TRIACII code for track measurements from SSNT detectors - Patiris, D. L.; Blekas, K.; Ioannides, K. G. (HNPS Advances in Nuclear Physics, 2020)
The expansion of TRIAC to TRIACII code will be described. Both codes have been developed for recognition and parameters measurements of particles’ tracks from images of Solid State Nuclear Track Detectors. While the first program considers the tracks as circles, TRIACII code, using image analysis tools, counts the number of tracks and depending on the current working mode classifies them according to their radii (Mode I- circular tracks) or their axis (Mode II- elliptical tracks), their mean intensity value (brightness) and their orientation. Hough transform techniques are used for the estimation of tracks’ number and their parameters which are able to give results even for overlapping tracks. The new program has been used for radon’s progeny behavior and alpha particles’ energy discrimination.